2020
DOI: 10.1080/19012276.2019.1710240
|View full text |Cite
|
Sign up to set email alerts
|

Social support, bullying, school-related stress and mental health in adolescence

Abstract: The current study aimed to examine the impact of social support, bullying and schoolrelated stress on both positive and negative aspects of mental health in adolescence. In addition, the possible buffering effects of social support related to school performance was investigated. The analyses were based on a cross-sectional survey of 1814 students between 15 and 21 years old from five upper secondary schools in Norway. Multiple hierarchical linear regression models with robust standard errors were estimated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 45 publications
5
39
2
3
Order By: Relevance
“…These findings support H4 and previous research (Sowislo and Orth, 2013;Yeoh et al, 2017). In addition, in support of H5, H6 and previous research (Alm and Låftman, 2018;Bearman and Stice, 2008;Låftman and Modin, 2012;Ringdal et al, 2020) appearance pressure and school stress had a direct and positive relationship with emotional problems. However, it was more surprising that these associations were somewhat stronger for boys compared with girls, even though the differences were small.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings support H4 and previous research (Sowislo and Orth, 2013;Yeoh et al, 2017). In addition, in support of H5, H6 and previous research (Alm and Låftman, 2018;Bearman and Stice, 2008;Låftman and Modin, 2012;Ringdal et al, 2020) appearance pressure and school stress had a direct and positive relationship with emotional problems. However, it was more surprising that these associations were somewhat stronger for boys compared with girls, even though the differences were small.…”
Section: Discussionsupporting
confidence: 90%
“…According to a study that compared the student reports on the perceptions of school pressure between 1994 and 2010, the level of perceived pressure did not increase during the period, except for a temporary uptake between 2002 and 2006. However, recent research indicates that the prevalence of adolescent experience of school stress has increased during the last decade (Bakken et al, 2018;Löfstedt et al, 2019), and that there is a clear association between school stress and emotional problems (Låftman and Modin, 2012;Ringdal et al, 2020).…”
Section: Appearance and School Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Bullying. The bullying scale was based on three items generated from the questionnaire for adolescents in the national Norwegian Survey on living Conditions 2012 [23] with additionally a new item assessing cyberbullying [17]. The bullying scale was pilot tested among adolescents in one upper-secondary school in Norway (n=479), with a response rate of 98% in the spring of 2016.…”
Section: Methodsmentioning
confidence: 99%
“…These schemas entail dysfunctional attitudes about self and the world, built upon negative experiences in people' s lives ( Beck, 1987) . Previous studies also revealed that adolescents with uncontrolled stress had poorer psychological well-being, and greater anxiety and depression symptoms ( Burger & Samuel, 2017;Hezomi & Nadrian, 2018;Ringdal et al, 2020).…”
Section: Discussionmentioning
confidence: 93%